A STUDY OF INDIA’S CAPITAL CONTROL REGIME AND ITS EFFECTIVENESS IN MANAGING CAPITAL FLOW VOLATILITY - A, Belaisch; Cullinane, K. B; Mason, K. J; Cape , M. B (Economics and Statistics Research Journal (ESRJ), 2022)
This study analyzes the effectiveness of capital controls in stabilizing capital flow volatility in India during global shocks, specifically the Global Financial Crisis (GFC) and the taper tantrum episode of 2013. Using data from the IMF’s Annual Report on Exchange Arrangements and Exchange Restrictions (AREAER), a capital controls index is constructed to examine changes in India’s capital control regime pre- and post-GFC. The study finds that the net capital control index eased before the GFC and increased after the GFC due to volatile capital inflows. The effectiveness of capital controls in reducing capital flow volatility in India is also explored and found to be highly effective, although their effectiveness is reduced during the post-GFC period. The paper documents the types and purposes of capital controls and the various changes in India’s capital control regime since its economic liberalization in 1991. The findings of the study support India’s strategy of a carefully calibrated approach to capital account management as emerging economies navigate financial market risks